On the Application of Big Data in Smart Transformation Enterprises - Ge, Shan (Transactions on Social Science, Education and Humanities Research, 2023)
The arrival of the digital informationization era heralds the issue of technological innovation in the intelligent transformation of enterprises, for different scenarios and different cases, the application of big data plays an important role in the accumulation of massive data, the issue of the reliability of the data and the form of data transformation with the transformation of the enterprise has undergone a significant change in the data processing software platform, and strive to deal with the accuracy and efficiency of the data is a multitude of Enterprises plan to achieve the goal, under the general software of big data, the introduction of data information software platform is undoubtedly an important initiative in today’s society in order to meet the massive data research. This paper summarizes the development and application of data information software platforms on the basis of awards, data as a prerequisite, put forward for intelligent platforms to monitor the systematic approach to the integration of the Sqoop framework in the Hadoop platform for the enterprise to formulate an intelligent data monitoring indicators of the processing model.